Unified Particle Swarm Optimization for Solving Constrained Engineering Optimization Problems - Parsopoulos, K. E.; Vrahatis, M. N. (Advances in Natural Computation, 2005)
We investigate the performance of the recently proposed Unified Particle Swarm Optimization method on constrained engineering optimization problems. For this purpose, a penalty function approach is employed and the algorithm is modified to preserve feasibility of the encountered solutions. The algorithm is illustrated on four well–known engineering problems with promising results. Comparisons with the standard local and global variant of Particle Swarm Optimization are reported and discussed.